Survival Improvement in Human Retinal Pigment Epithelial Cells via Fas Receptor Targeting by miR‐374a. Issue 12 (20th June 2017) - Tasharrofi, Nooshin; Kouhkan, Fatemeh; Soleimani, Masoud; Soheili, Zahra‐Sheila; Kabiri, Mahboubeh; Mahmoudi Saber, Mohaddeseh; Dorkoosh, Farid Abedin
ABSTRACT: Oxidative conditions of the eye could contribute to retinal cells loss through activating the Fas‐L/Fas pathway. This phenomenon is one of the leading causes of some ocular diseases like age‐related macular degeneration (AMD). By targeting proteins at their mRNA level, microRNAs (miRNAs) can regulate gene expression and cell function. The aim of the present study is to investigate Fas targeting by miR‐374a and find whether it can inhibit Fas‐mediated apoptosis in primary human retinal pigment epithelial (RPE) cells under oxidative stress. So, the primary human RPE cells were transfected with pre‐miR‐374a pLEX construct using polymeric carrier and were exposed to H2 O2 (200 μM) as an oxidant agent for induction of Fas expression. Fas expression at mRNA and protein level was evaluated by quantitative real‐time PCR and Western blot analysis, respectively. These results revealed that miR‐374a could prevent Fas upregulation under oxidative conditions. Moreover, Luciferase activity assay confirmed that Fas could be a direct target of miR‐374a. The cell viability studies demonstrated that caspase‐3 activity was negligible in miR‐374a treated cells compared to the controls. Our data suggest miR‐374a is a negative regulator of Fas death receptor which is able to enhance the cell survival and protect RPE cells against oxidative conditions. J. Cell. Biochem. 118: 4854–4861, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Aging is accompanied by raised ROS level in the eye which in part can change the normal miRNA profile and expression of some proteins, like Fas death receptor in the retinal pigment epithelial cells (RPE cells). In the present study, it was shown that miR‐374a by targeting Fas receptor can protect the RPE cells from oxidant‐induced apoptosis and enhance cell viability.